Security Approach for Data Storage and Retrival in The Cloud - Basak, Somnath; Dey, Somnath; Deb, Mrinmay (International Journal of Computer Sciences and Engineering, 2018)
Since the beginning of courtesy, man has always been motivated by the need to make advancement and better the existing technologies. This has led to remarkable development and progress which has been a launching pad for further evoluation of all the momemtous advances made by society from the beginning till date. Cloud computing is the concept of using outlying services through a network using various resources. It is basically meant to give maximum with the minimum resources i.e. the user end is having the minimum hardware requirement but is using the maximum capability of computing. This is possible only through this technology which requires and utilizes its resources in the best way. But this advantage comes at a cost. Firstly, the data is uploaded insecurely which has a high risk of being hacked by some malicious people. Secondly, the data saved at outlying servers is under the surveillance of unauthorized people who can do anything with our data and Information. So, these data security risks are causing a barrier in the development of the area of cloud computing infrastructure. In this paper we have discussed about the various techniques by which we can enhance the cloud service in relation to security and data privacy and also designed a new effective cloud data security infrastructure.